Moral hazard among the employed: Evidence from regression discontinuity - Jonas Jessen; Robin Jessen; Andrew Johnston; Ewa Gałecka-Burdziak (RWI - Leibniz-Institut für Wirtschaftsforschung, 2025)
We exploit policy discontinuities in Poland's unemployment insurance to examine the causal effect of changes to both benefit durations and levels. Using a regression discontinuity approach, we uncover three findings: (1) Higher benefit levels distort employment more than benefit extensions. (2) Benefit durations and levels interact: Longer durations substantially increase the distortionary effect of more generous payments. (3) Higher payments increase the transition of employed workers into unemployment. We develop a model of optimal unemployment insurance that accounts for moral hazard among both employed and unemployed workers. Notably, for level increases, distortionary costs are larger among the employed than unemployed. – – Wir nutzen politische Diskontinuitäten in der polnischen Arbeitslosenversicherung, um die kausale Wirkung von Änderungen der Leistungsdauer und -höhe zu untersuchen. Unter Verwendung eines Regressionsdiskontinuitätsansatzes kommen wir zu drei Ergebnissen: (1) Höhere Leistungsniveaus verzerren die Beschäftigung stärker als Leistungsverlängerungen. (2) Die Dauer der Leistungsgewährung und Niveaus interagieren: Längere Laufzeiten erhöhen die verzerrende Wirkung großzügigerer Zahlungen. (3) Höhere Zahlungen erhöhen den Übergang von Erwerbstätigen in die Arbeitslosigkeit. Wir entwickeln ein Modell für eine optimale Arbeitslosenversicherung, das das moralische Risiko sowohl bei Beschäftigten als auch bei Arbeitslosen und arbeitslosen Arbeitnehmern berücksichtigt. Bei einer Erhöhung des Niveaus sind die verzerrenden Kosten bei den Beschäftigten größer als bei Arbeitslosen.
Keywords: H55; J20; J65; 330; Unemployment insurance; spell duration; regression discontinuity; endogenous separations